1975
DOI: 10.1007/bf00316525
|View full text |Cite
|
Sign up to set email alerts
|

Ver�nderungen von Durchblutung und oxydativem Stoffwechsel des Gehirns bei Patienten mit einer Demenz

Abstract: The purpose of this retrospective study was to investigate how the blood flow and oxidative metabolism of the brain was changed in dementia and the influence of the age factor. Cerebral blood flow (CBF) was measured in 115 patients aged from 40 to 83 years by means of the Kety-Schmidt technique with the modification of Bernsmeier and Siemons. The cerebral metabolic rates of oxygen and CO2 were determined by the van Slyke method and by gaschromatography respectively and of glucose and lactate by standard enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1977
1977
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Hachinski et al (16), with the xenon‐133 technique, found that the cerebral blood flow in vascular (multi‐infarct) dementia was reduced, whereas that in degenerative dementia was normal. Hoyer et al (17), with the Kety‐Schmidt technique, found three types of cerebral blood flow (decreased, normal, increased) in a large group of nonspecified dementias. It is noteworthy that in the present study the systolic and diastolic blood velocities in many of the degenerative dementia patients were 50–100 percent greater than the velocities in either the vascular dementia or the nondemented patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hachinski et al (16), with the xenon‐133 technique, found that the cerebral blood flow in vascular (multi‐infarct) dementia was reduced, whereas that in degenerative dementia was normal. Hoyer et al (17), with the Kety‐Schmidt technique, found three types of cerebral blood flow (decreased, normal, increased) in a large group of nonspecified dementias. It is noteworthy that in the present study the systolic and diastolic blood velocities in many of the degenerative dementia patients were 50–100 percent greater than the velocities in either the vascular dementia or the nondemented patients.…”
Section: Discussionmentioning
confidence: 99%
“…Der ausbleibende Konzentrationsanstieg der Kreatin-Kinase als ein intrazelluläres Enzym bestätigt unter Berücksichtigung der stabilen perioperativen Kreislaufbedingungen und dem Ausbleiben von Durchgangssyndromen, daß es bei den untersuchten Patienten nicht zu einem manifesten zerebralen Nervenzeiischaden gekommen ist. Die perioperativen Konzentrationsverläufe der untersuchten Parameter lassen vermuten, daß es intraoperativ über eine Störung der Sauerstoffutilisation (ischämische Penumbra) zu einer Verminderung der intrazellulären Energiegewinnung gekommen ist, wobei nicht klar ist, welches die Ursachen der gestörten Sauerstoffutilisation sind (2,3,13,24,26). Eine solche Penumbra sollte aber in ihrer klinischen Relevanz nicht unterschätzt werden, da moderne Gedächtnistheorien dem Bewußtsein und damit auch bestimmten Bewui3tseinsstörungen nicht mehr definierte Gehirnareale zuordnen (16,17,25).…”
Section: Diskussionunclassified
“…Die Diagnosen ,,zerebrale Durchblu tungsstörungen", ,,lerebro-vaskuläre InsuffIZienz" und "Zerebralsklerose" werden im klinischen Alltag und in der Praxis oft mit einer gewissen Großzügigkeit gestellt, obwohl weder das objektiv feststellbare Korrelat -Hirndurchblutung bzw. Hirnstoffwechsel -noch der pathoanatomische Befund bekannt sind (48) Unter den arteriosklerotisch bedingten Störungen stehen Veränderungen vom Multi-infarct-Typ im Sinne eines Status lacunaris, hervorgerufen durch zahlreiche Mikroinfarkte im Stammganglienbereich und in der Brücke, im Vordergrund. Klinisch ist die Erkrankung gekennzeichnet durch eine schlecht artikulierte Sprache, durch mangelnde Beweglichkeit der Zunge und ausgeprägte Behinderung des Schluckaktes, wobei wir psychopathologisch Zwangslachen, Zwangsweinen und Grimassieren finden können.…”
Section: Vaskuläre Ursachenunclassified